PRINTING OF KARAIM BOOKS: PAST AND PRESENT - Kobeckaitė, Halina (Knygotyra, 2016)
The main aim of this article is to briefly overview the history of printed books of Karaims in Eastern Europe and Crimea, taken in a very broad sense both in Karaim and in other languages. The Karaim language belongs to the Kipschak’s (Kuman’s) family of Turkic languages. Printing of books in the native language, to be used both in everyday life and for religious purposes, was an important activity of Karaim communities. According to the geographical settlements of Karaims in Europe, there existed three dialects of the Karaim language – Crimean, Lutsk-Halich (Ukraine) and Trakai (Lithuania) dialect. Books were printed in each of these dialects in different periods of time, depending on the political situation. In the very beginning of printing era, Crimean Karaims were the most active ones. In the 16th century they started printing books, and then continued during the 18th–19th centuries. Later it was Vilnius and Lutsk that took over. At the end of 19th – beginning of 20th centuries, and especially between the two world wars, Karaim scholars and spiritual leaders in Vilnius and Lutsk were very active investigating and popularising their cultural heritage. Due to their achievements, revival of national identity and revitalization of scientific studies on national heritage after 1990 became very productive. Several Karaim figures of the 20th century were important, among them Hadgi Seraya Khan Shapshal (1873–1961), the highest priest, a famous turkologist, prof. Ananiasz Zajączkowski (1903–1970) and two senior priests Simonas Firkovičius (1897–1982) and Mykolas Firkovičius (1924–2000). All printed Karaim books are important sources for understanding the Karaim cultural heritage and for continuity of the communities’ life.
Keywords: ...